2011
DOI: 10.1111/j.1744-7917.2011.01457.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of selection for early and late reproduction on metabolite pools in Acanthoscelides obtectus Say

Abstract: The present study was aimed at revealing the responses of metabolite pools to selection for alternative reproductive schedules in the seed beetle, Acanthoscelides obtectus Say (Coleoptera: Chrysomelidae: Bruchinae). The levels of metabolites (free sugars, glycogen, lipids, soluble and hydrophobic proteins) that were determined in virgin females and males at three ages from adult eclosion onwards were compared among the base population (B) and two derived lines that were selected for either early (Y) or late (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…Increased complex III activity could also be beneficial if metabolic reprogramming of L beetles toward accumulation of lipids and carbohydrates (Lazarević et al. ) involves higher entrance of electrons to the respiratory chain through FAD‐linked dehydrogenases that bypass complex I (Lenaz et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased complex III activity could also be beneficial if metabolic reprogramming of L beetles toward accumulation of lipids and carbohydrates (Lazarević et al. ) involves higher entrance of electrons to the respiratory chain through FAD‐linked dehydrogenases that bypass complex I (Lenaz et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…), and metabolite content (Lazarević et al. ). We found this to be true for ETC activity as well, as sexual dimorphism in LL lines were higher than in EE lines for all complexes (Storer's SD index; ETC I: −0.14 vs. −0.12; ETC II: −0.22 vs. −0.12; ETC III: −0.04 vs. 0.02; ETC IV: −0.19 vs. 0.08).…”
Section: Discussionmentioning
confidence: 99%
“…These E and L populations have been used in previous studies to investigate various aspects of life history evolution, such as demographic and physiological aspects of ageing and reproductive behaviour (Tucić et al 1996(Tucić et al , 1997Š ešlija et al 1999;Maklakov et al 2005;Šešlija et al 2009;Lazarević et al 2012;Stojković et al 2011Stojković et al , 2014. It has been repeatedly demonstrated that individuals from the L populations live substantially longer, have higher egg-to-adult viability, longer developmental time, higher body weight and total fecundity relative to the E beetles.…”
Section: Introductionmentioning
confidence: 96%
“…In line with this interpretation, Lazarević et al. () showed that the consumption of metabolite resources is retarded during adult ageing in bean beetles from L lines. Here, we confirm that bean beetles selected for early reproduction have indeed evolved a markedly higher MR. Below, we discuss some more specific insights gained by our experiments.…”
Section: Discussionmentioning
confidence: 73%
“…These differences in sex‐ and age‐specific MR are well matched by the sex‐ and age‐specific availability of primary metabolic substrates (i.e. lipids), which is higher in males than in females but decreases with age more rapidly in L line males than in L line females (Lazarević et al., ). We note that the costs of mating and mate searching to males are substantial in this group of insects (Berger et al., ; Immonen, Liljestrand‐Rönn, et al., ; Paukku & Kotiaho, ; Salehialavi, Fritzsche, & Arnqvist, ) and male investment in costly ejaculates decreases with age (Fox, Hickman, Raleigh, & Mousseau, ; Immonen, Collet, Goenaga, & Arnqvist, ).…”
Section: Discussionmentioning
confidence: 99%